Cathodic Behaviour of Cysteine at a Platinum Electrode - Barroso,M. Fátima (2007)
The electroreduction behaviour of cysteine was investigated using cyclic, square wave and differencial pulse voltammetric techniques at a platinum working electrode. The reduction of cysteine occurs at a potential of -0.36 V independent of pH. It is a reversible process, controlled mainly by diffusion and in the mechanism of reduction 1 electron per molecule is involved. Using the voltammetric techniques: Cyclic Voltammetry, Square Wave Voltammetry and Differencial Pulse Voltammetry, different parameters (pH, frequency, step potential, pulse amplitude, scan rate) were optimized in order to develop an electrochemical procedure for determination of cysteine in pharmaceutical products. The repeatability, reproducibility, precision and accuracy of the methods were studied. No electroactive interferences from the excipient were found in the pharmaceutical compounds.